Muslim Minorities and Political Representation In the 2019 Bali Provincial Regional Representative Council Election - Ali Sodiqin; Nurdhin Baroroh (IN RIGHT: Jurnal Agama dan Hak Azazi Manusia, 2025)
This study explored the success of the Balinese Muslim minority in winning the 2019 Regional Representative Council (DPD) election. The primary focus is to identify the factors that influenced this triumph and analyze the strategies employed and the roles played by the actors involved. This study uses a phenomenological approach complemented by Higley and Burton's elite theory. This theory explained the dynamics between actors through two distinct paths, namely "elite settlement" and "elite convergence." The results showed that, first, the reasons underlying the determination of HBS as a DPD candidate from among Muslims are (1) Muslims constitute approximately 10-13% of Bali's population, necessitating representation at the central or national level, (2) HBS's candidacy was determined based on their electability during the candidate screening process, (3) The agreement of Muslim leaders from diverse religious, social organizations, and Islamic political parties in Bali played a crucial role in the nomination. Second, the nomination of HBS through the elite settlement path was successful, as evidenced by the unified support of Muslim elites for a single candidate. However, the elite convergence route encountered challenges, resulting in an unexpected impact on HBS's vote acquisition. The election of HBS shows the ability of the Balinese people, who are multi-cultural and multi-religious, to manage democracy without causing polarization in society.